A Reinforcement Learning Based Approach for Efficient Routing in Multi-FPGA Platforms - Umer Farooq; Habib Mehrez; Najam Ul Hasan (Sensors)
Prototyping using multi-FPGA platforms is unique because of its use in real-world testing and cycle-accurate information on the design. However, this is a complex and time-consuming process with multiple sub-steps. Among its sub-steps, inter-FPGA routing is the one that can take a significant percentage of total prototyping time. The share of inter-FPGA routing is projected to increase further over time with the ever-increasing complexity of the target designs. In this work, we propose to integrate a Reinforcement Learning (RL)-based framework to speed up the inter-FPGA routing process. For this purpose, we first find a trade-off between the exploration and exploitation approach (also termed as the <semantics>ϵ</semantics>-greedy approach) in our RL-based framework while not affecting the final Quality of Results (QoR). To gauge its effectiveness, we then perform an extensive comparison between the proposed framework and established routing approaches. In this regard, a set of fourteen complex benchmarks is used, and the results of the proposed framework are compared against existing routability- and timing-driven routing approaches. Experimental results reveal that, on average, the proposed RL-based framework speeds up the inter-FPGA routing process by 45% and 32%, compared to routability- and timing-driven routing approaches, respectively. The speedup at the routing step further leads to an overall speedup of the backend flow by 22% and 15%, respectively.